Plasticizer-induced enhanced electromechanical performance of natural rubber dielectric elastomer composites. (28th July 2020) - Ni, Yufeng; Yang, Dan; Wei, Qungui; Yu, Liyuan; Ai, Jia; Zhang, Liqun
Abstract: Herein, high-dielectric-constant titanium dioxide (TiO2 ) nanoparticles, modified by γ-methacryloxypropyl trimethoxy silane (referred as mTiO2 ) and polar dioctyl phthalate (DOP), were introduced into natural rubber (NR) to obtain high-performance dielectric elastomer composites. The incorporation of DOP sharply decreased the elastic modulus of mTiO2 /NR composites by decreasing the entanglement between NR chains and weakening the enforcement effect of mTiO2 nanoparticles. At the same time, highly polar DOP improved the dielectric constant of mTiO2 /NR composites and resulted in high electromechanical sensitivity ( β ). Finally, a large actuated strain of 25.3% has been rendered by 50 phr DOP/mTiO2 /NR composite at 40 kV/mm, which is 10 times higher than pure NR (2.6%) under the same electric field. The present study reveals that the plasticizer-enhanced flexibility of inorganic dielectric filler/polymer composites is an effective method to enhance the electromechanical performance of dielectric elastomer actuators.